The effect of calibration factor geometries on the accuracy of 99mtc spect activity quantification - Azmi, Azmin Nur Aina (2025)
Quantitative SPECT imaging has become increasingly important in disease diagnosis and monitoring. Achieving accurate absolute quantification of radiotracer distribution is essential for dosimetry-based personalized radionuclide therapy. A key determinant of SPECT/CT quantification accuracy is the calibration factor (CF). This study aimed to evaluate the impact of CFs and recovery coefficients (RCs) derived from different calibration geometries on SPECT/CT quantification accuracy. Three phantom geometries were assessed: a petri dish filled with 99mTc (Geometry 1), a whole body NEMA phantom filled with 99mTc (Geometry 2), and a sphere filled with 99mTc attached to the cylindrical in NEMA phantom (Geometry 3). CFs were calculated for each geometry, and RCs were obtained for six spheres with varied diameters (1.0 to 3.7 cm). Quantification errors were analysed both before and after the application of partial volume correction (PVC). Geometry 1 yielded the highest CF, primarily due to the use of a different activity concentration. This resulted in lower RCs and greater quantification errors, largely attributable to pronounced PVE. Consequently, the results from Geometry 1 are not directly comparable to those of the other geometries due to the disparity in activity concentration. Geometry 2 demonstrated the most accurate and consistent RCs reaching values as high as 1.03 indicating optimal conditions for quantification. Geometry 3 yielded moderate performance, although spill-in effects were observed at smaller sphere sizes. PVC substantially improved quantification for small spheres across all geometries. However, overestimation errors emerged in larger volumes, especially in Geometries 1 and 3. In conclusion, the choice of calibration geometry has a significant influence on the quantitative accuracy of SPECT/CT imaging. These findings highlight the importance of selecting appropriate calibration strategies and applying geometry-specific corrections to improve clinical accuracy in radionuclide therapy.